2022
DOI: 10.1111/exd.14582
|View full text |Cite
|
Sign up to set email alerts
|

Ustekinumab reduces serum protein levels associated with cardiovascular risk in psoriasis vulgaris

Abstract: Psoriasis increases the risk of cardiovascular disease (CVD). Biomarkers for cardiovascular (CV) risk stratification in psoriasis are lacking, and the effects of psoriasis biologics on CV risk reduction remain unclear. The goal of this study was to identify biomarkers of CV risk in psoriasis blood that are reduced by ustekinumab. We quantified 276 inflammatory and CV‐related serum proteins with Olink's multiplex assay in 10 psoriasis patients (vs. 18 healthy controls) and after 12 weeks of ustekinumab treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 87 publications
0
3
0
2
Order By: Relevance
“…With our proteomics substudy, we intended to pave the way in discovering pharmacodynamic signatures capable of predicting GUS response. Despite using a sample size comparable to other Olink® studies [36][37][38][39][40] and that the Olink® assay was able to identify DEPs (e.g. between psoriasis patients and healthy controls), we could not identify predictive candidates with the chosen protein panel.…”
Section: Discussionmentioning
confidence: 93%
“…With our proteomics substudy, we intended to pave the way in discovering pharmacodynamic signatures capable of predicting GUS response. Despite using a sample size comparable to other Olink® studies [36][37][38][39][40] and that the Olink® assay was able to identify DEPs (e.g. between psoriasis patients and healthy controls), we could not identify predictive candidates with the chosen protein panel.…”
Section: Discussionmentioning
confidence: 93%
“…В таких случаях назначение устекинумаба может быть более эффективным и предпочтительным -как за счет патогенетического воздействия на широкий спектр ключевых провоспалительных цитокинов, так и по причине невлияния на риск развития серьезных сердечно-сосудистых событий на фоне терапии [38,39]. В этой связи интересны результаты исследований, согласно которым блокада IL-12/IL-23 может кратковременно уменьшать воспаление аортальных сосудов с более стойким снижением продукции воспалительных цитокинов, связанных с сердечно-сосудистыми заболеваниями [22,40]. Кроме того, метаанализ последних исследований показал, что устекинумаб является более эффективным по сравнению с другими ГИБП и «классическими» иммуносупрессорами у пациентов с псориазом и сопутствующим ожирением [41].…”
Section: Discussionunclassified
“…Initial studies seemed to show an increased risk of MACE associated with this drug but were soon disproved [ 40 ]. Contrarily, recent studies show that ustekinumab has a cardioprotective effect, as its use for 12 weeks reduces blood levels of several proteins elevated in psoriasis and associated with inflammation and cardiovascular risk, such as E-selectin, von Willebrand factor, IL-6 and myeloperoxidase [ 43 ]. Regarding adipokines, Onsun et al observed that during 48 weeks of therapy blood levels of leptin, adiponectin and omentin were significantly higher in ustekinumab-treated patients than in anti-TNF-treated patients, although these values correlated positively with response rates to therapy [ 44 ].…”
Section: Biologic Drugs and Cardiovascular Complicationsmentioning
confidence: 99%